Current issues in aquaculture: lessons from Malaysia - Fathi, Sharihan; Harun, Aizul Nahar; Rambat, Shuib; Tukiran, Nur Azira (American Scientific Publishers, 2018)
Aquaculture in Malaysia has become a top 15 of global producers with 521,000 tonnes of total aquaculture production. As a world producer, it is crucial to learn the foundation and current challenges encountered by the sector. This paper address six major issues and challenges of the aquaculture sector in Malaysia specifically issues of fish stock depletion, climate changes, current diseases, media influences in the sector, non-compliance feeding practiced and poor interaction between stakeholders. The methodology involves searching the divergent trusted database and related information using a most popular search engine that covers selected journals including resources from fisheries authorities: Department of Fisheries Malaysia, Food, and Agriculture Organization of The United Nation and WorldFish Center. A combination of this findings, newest technology application will be suggested as accurate and timely information on managing aquaculture systems.